Sleep-Related Breathing Disorders: When CPAP Is Not Enough. - Selim, Bernardo; Ramar, Kannan (Neurotherapeutics, 2021)
Three decades ago, continuous positive airway pressure (CPAP) was introduced to treat obstructive sleep apnea (OSA). Shortly after, bilevel positive airway pressure devices (BPAP) that independently adjusted inspiratory and expiratory positive airway pressure were developed to treat complex sleep-related breathing disorders unresponsive to CPAP. Based on the bilevel positive airway pressure platform (hardware) governed by propriety algorithms (software), advanced modes of noninvasive ventilation (NIV) were developed to address complex cardiorespiratory pathophysiology beyond OSA. This review summarizes key aspects of different bilevel PAP therapies (BPAP with/without backup rate, adaptive servoventilation, and volume-assured pressure support) to treat common sleep-related hypoventilation disorders, treatment-emergent central sleep apnea, and central sleep apnea syndromes.